Navigating compliance challenges in African regional integration - Nyirongo, Raisa (Department of Commercial Law, 2024)
Regional integration has been pursued on the African continent for decades, with the goal of developing and uniting the continent. The determination of African leaders to implement a system of integration is evidenced by the establishment of multiple regional economic communities across the continent. One notable issue, however, is that the results attained thus far do not correspond with the efforts made. African states have seen minimal returns in comparison to the predicted benefits regional integration promised to offer. The slow progress has been attributed to, among other reasons, a lack of compliance by member states. This thesis seeks to investigate the relationship, if any, between compliance systems of RECs and the effectiveness of the community. It is recognised, on one hand, that member states have an obligation to comply with and implement community obligations. Conversely RECs have a role to play in developing systems that promote compliance within the community. The research consists of a desk review of the founding treaties of the African Union, the Sothern African Development Community, the Common Market for Eastern and Southern Africa, and the East African Community. The study analyses the systems RECs have established to promote compliance, specifically the rules systems, compliance information systems and non-compliance response systems. The research found that rules are vague and empower executive organs with great authority; RECs do not have established monitoring mechanisms, except for the AU; and there is a gap in reporting of compliance by member states. Following the analysis of compliance reporting and monitoring, the study investigates the role of community courts in enforcing community obligations. It was found that many community courts have been limited in their powers, rendering them incapacitated in enforcing community obligations. The research concludes that there is a link between compliance systems and the effectiveness of a community. To improve effectiveness, the research recommends the development of suitable compliance systems including implementing a compliance report that can be submitted by member states both regionally and at the continental level. This research contributes to the literature on regional integration, law and development in Africa. It aims to provide insight to policy makers responsible for decisions related to the design of compliance systems within regional economic communities.